Performance of amorphous silicon double junction photovoltaic systems in different climatic zones - Ralph Gottschalg; Christian N. Jardine; R. Ruther; Tom Betts; G.J. Conibeer; J. Close; David Infield; Michael J. Kearney; K.H. Lam; Kevin Lane; H. Pang; R. Tscharner (2002)
To date the majority of investigations into the performance of amorphous silicon photovoltaic systems have been limited to single sites, and therefore the conclusions from such studies are unlikely to be as generic as they might at first appear. This paper compares data collected from different systems across the world in Brazil, Hong Kong, Spain, Switzerland, and the United Kingdom. All systems have been operating for a number of years, and are employing double junction amorphous silicon devices of a similar age manufactured by RWE Solar. The data are analysed for performance variations reflecting the different climatic zones, and the variations are explained on the basis of operating temperature, incident irradiation and seasonal spectral shift.